2011
DOI: 10.1586/erp.11.78
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diabetes mellitus on healthcare costs in Italy

Abstract: Diabetes mellitus is an increasingly common chronic disease that has a great impact not only in terms of clinical effects, but also in terms of economic burden worldwide. Expenditures due to diabetes derive essentially from direct and indirect costs. Current estimates of global healthcare expenditures due to diabetes are US$376 billion and are expected to increase to US$490 billion by 2030. In particular, costs associated with diabetes-related complications represent the most relevant part of the national heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 43 publications
0
15
0
1
Order By: Relevance
“…This latter factor significantly increased the costs associated with diabetes by factors of 3, 5 and 10 when the patient had microvascular complications, macrovascular complications or both, respectively, compared with patients who had no complications. Giorda et al [45] suggested that effective therapy with good metabolic control can reduce the risk of complications and is an economically valid strategy. With the limitations mentioned above, our results are in line with all these results.…”
Section: Discussionmentioning
confidence: 99%
“…This latter factor significantly increased the costs associated with diabetes by factors of 3, 5 and 10 when the patient had microvascular complications, macrovascular complications or both, respectively, compared with patients who had no complications. Giorda et al [45] suggested that effective therapy with good metabolic control can reduce the risk of complications and is an economically valid strategy. With the limitations mentioned above, our results are in line with all these results.…”
Section: Discussionmentioning
confidence: 99%
“…ACCEPTED MANUSCRIPT 5 While a variety of detection methods, including electrochemical [9][10][11], chemiluminescence [12,13] and fluorescence [14,15], have been investigated, comparatively simple colorimetric methods (which have a long history) are still attractive because the output of these assays can be visually observed and compared to a color chart to generate low-cost, rapid, semi-quantitative results. Truly quantitative detection of these paper based colorimetric reactions requires the use of bench top scanners [16] or cameras combined with computer-based image analysis software [17,18], or other sophisticated commercially available greyscale or color intensity measuring instruments.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Global healthcare expenditures for diabetes alone are expected to reach $490 billion by 2030, while the number of diabetes cases worldwide will double between 2000 and 2030 to over 400 million people [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Direct costs include costs of patient's hospitalization and care. Indirect costs involve income reduction, personal abilities decrease, long-term inability, and early death (5). Global burden of noncontagious diseases such as diabetes is considerably increasing.…”
Section: Introductionmentioning
confidence: 99%